Квантифікаційні методики дослідження системи стримувань і противаг - Забавська, Христина; Zabavska, Khrystyna (Видавництво Львівської політехніки, 2019)
Розглянуто основні квантифікаційні методики дослідження системи стримувань і противаг. Враховуючи основні історичні етапи розвитку ідей щодо функціонування системи стримувань і противаг, основуючись на порівняльному методі, окреслено основні особливості розуміння функціонування окремих аспектів системи стримувань і противаг за допомогою використання математичних методів. Запропоновано класифікацію методів кількісного дослідження, а також методики вивчення рівня президентської влади, порівняльні методики повноважень президента і парламенту, методики розрахунку парламентських повноважень. Усі характерні особливості застосування цих методик критично проаналізовано. Зміст кожної методики кількісного аналізу системи стримувань і противаг детально окреслено, а особливу увагу приділено основним недолікам їх використання під час вивчення системи стримувань і противаг загалом.

The article deals with the main quantification methods of the system of checks and balances. Taking into account the main historical stages of the development of ideas concerning the functioning of the checks and balances system, on the basis of the comparative method, the main features of understanding the functioning of different aspects of checks and balances system by using mathematical methods are emphasized. Having systematized mathematical techniques, the author of the article offers its own typology on the basis of highlighted criteria. The classification of quantification methods including methods of studying the level of presidentialism, methods to compare the powers of the president and parliament, methods related to the calculation of parliamentary powers, is proposed. The features and peculiarities of all these methods are critically considered in the article. Each quantification methods is analyzed in detail and special attention in the article is paid to the main the disadvantages of their use in the study of checks and balances system as a whole. The article provides a description of the technics and formulas used in the application of each of methods. It is emphasized that a part of the methods are used to rank the states in the form of government, while another part is used to index and create a common list of states by this or that index accordingly. But all of these methods are focused on a specific component of the checks and balances system and are aimed at the sphere of the influence of a separate political player indexing. A comprehensive mathematical method for the system of checks and balances as a basic guarantee of democratic functioning needs to be proposed
Quantification methods of the checks and balances system study
Keywords: стримування; противаги; методика; чисельні методи; індекс; гілки влади; кластерний аналіз; ранжування; система; формула; checks; balances; method; quantification methods; index; branches of power; cluster analysis; ranking; system; formula; 321.7